Linguocultural Features of English Abbreviations - Qizi, Gavharoy Isroiljon; Azizbek, Sharobiddinov (European Journal of Life Safety and Stability (2660-9630), 2021)
In this article is given more information about structure of abriviations. It deals the linguacultural peculiarities of abriviations in English and how to teach them effectively.